2017
DOI: 10.1038/cddis.2017.474
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/calmodulin-dependent kinase kinase 2 regulates hematopoietic stem and progenitor cell regeneration

Abstract: Hematopoietic stem and progenitor cells (HSPCs) are predominantly quiescent in adults, but proliferate in response to bone marrow (BM) injury. Here, we show that deletion of Ca2+/calmodulin (CaM)-dependent protein kinase kinase 2 (CaMKK2) promotes HSPC regeneration and hematopoietic recovery following radiation injury. Using Camkk2-enhanced green fluorescent protein (EGFP) reporter mice, we found that Camkk2 expression is developmentally regulated in HSPC. Deletion of Camkk2 in HSPC results in a significant do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Immunoblots were prepared as published ( 24 ). The following primary antibodies were used in this study: purified mouse anti-CaM kinase kinase (BD Biosciences, CA, USA), anti-phospho-AMPK alpha (T172 40H9) rabbit mAb, anti-AMPK alpha (F6) mouse mAb, anti-phopho-Stat3 (Tyr705 D3A7) rabbit mAb, anti-Stat3 (124H6) mouse mAb, anti-β actin mouse mAb (all from Cell Signaling, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoblots were prepared as published ( 24 ). The following primary antibodies were used in this study: purified mouse anti-CaM kinase kinase (BD Biosciences, CA, USA), anti-phospho-AMPK alpha (T172 40H9) rabbit mAb, anti-AMPK alpha (F6) mouse mAb, anti-phopho-Stat3 (Tyr705 D3A7) rabbit mAb, anti-Stat3 (124H6) mouse mAb, anti-β actin mouse mAb (all from Cell Signaling, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Outside the brain, CaMKK2 is expressed at detectable levels restricted to a small subset of cell types, including hematopoietic stem and progenitor cells (HSCP) and mature myeloid cell subsets such as circulating monocytes and macrophages ( 22 ). CaMKK2 also regulates granulopoiesis and recently we have demonstrated that this kinase controls HSCP regeneration following bone marrow injury ( 23 , 24 ). Interestingly, CaMKK2 impinges the activation program of macrophages, and consequently, genetic ablation of Camkk2 attenuates the detrimental inflammatory response induced by bacterial endotoxin or obesity ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies of CaMKK2 in cancer have focused on its cancer cell intrinsic activities. However, this enzyme is also expressed within hematopoietic stem and progenitor cells, and in more mature myeloid cells, including monocytes and peritoneal macrophages 11,2123 . Furthermore, genetic ablation of Camkk2 in mice revealed an important role for this enzyme in the development of myeloid cells and in regulating their ability to mount inflammatory responses to various stimuli 22,24 .…”
Section: Introductionmentioning
confidence: 99%
“…The C-terminal region of STIM1 gates Orai/TRPC channels and stimulates Ca 2+ entry that could be important for cell fate decisions that are required during stem cells development and function. Ca 2+ entry through SOCC is critical for the activation of calmodulin-dependent protein kinase II (CAMK-II), and CAMK-II is shown to regulate the regeneration of hematopoietic stem and progenitor cells 22 . Similarly, Ca 2+ entry is also critical for switching from quiescence to cell cycle activation and Ca 2+ -dependent pathways are shown to modulate stem cell divisions 23 .…”
Section: Introductionmentioning
confidence: 99%